Bacterial contamination on raw vegetables from different Supermarkets at Kuala Pilah, Negeri Sembilan / Nurfazliza Mohd Fauzee - Mohd Fauzee, Nurfazliza (2017)
Raw vegetables have always been consumed for their health benefits. Increasing in foodborne disease related to raw vegetables are in alarmed conditions. This study was conducted to determine the bacterial contamination on raw vegetables from different supermarkets. The study of bacterial contaminations on raw vegetables sampling took place in Kuala Pilah, Negeri Sembilan. The sampling site would be three different supermarkets situated in Kuala Pilah. The ongoing study was conducted from September until December 2016. Three different selective differential medium were used to isolate Escherichia coli, Salmonella spp., and Staphylococcus aureus. Further characterization by observation and also Gram staining were done. Additional biochemical tests were performed. E.coli, Salmonella spp. and Staphylococcus aureus contaminations were found to be the highest on Psophocarpus tetragonolobus, Brassica oleracea and Lactuca sativa respectively. While for supermarkets, the highest contaminations of all three bacterial species were found at supermarket 2.